PENGATURAN PELAKSANAAN PASAL 209 KOMPILASI HUKUM ISLAM TENTANG WASIAT WAJIBAH TERHADAP ANAK ANGKAT MELALUI AKTA YANG DIBUAT NOTARIS DALAM BENTUK NOTARIIL - Yanuar Dwiyan Putra; Sri Endah Wahyuningsih (Jurnal Akta, 2017)
Research on "Implementation Arrangement of Article 209 Compilation of Islamic Law About Testament Required To Child Lift Through Notary Act Notarized In Notarial Form" aims To know and analyze the basic law of mandatory testament to adopted child in terms of Islamic inheritance law and Compilation of Islamic Law, To know and analyzing the legal consequences of the mandatory provision of the adopted child, To know and analyze the notary's responsibility as a mandatory certificate deed for adopted children.The basis of the law of provision of natural must must be preceded by the love and affection of adoptive parents to adopted children, so that parents want to be fair to their adopted children. The will is basically only given to the heirs who do not receive the inheritance due to being heaved by the heirs who are closer to the heirs. Provision of a mandatory will to an adopted child if it is based on Article 209 paragraph (2) of the Compilation of Islamic Law shall not cause any legal consequences resulting in a dispute between the adopted child and the principal heir of the heir. Because in Article 209 paragraph (2) Compilation of Islamic Law explains "Against adopted child who does not receive will is given a will as much as 1/3 of the inheritance of his adoptive parents". Notary besides being responsible in making the deed of will is also responsible in its implementation.Keywords: Wills Wajibah, Adopted Children, Compilation of Islamic Law, Notary Public